Surface heat flow in bestern Anatolia (Turkey) and implications to the thermal structure of the Gediz Graben - AKKOYUNLU, BÜLENT OKTAY; ERKAN, KAMİL; TAYANÇ, METE (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2022)
Knowledge of heat flow density on the Earth's surface and subsurface temperature distribution is essential for the interpretation of several processes in the crust such as for the evaluation of the geothermal potential of a region. With this study, we investigate the conductive heat flow distribution in western Anatolia to understand the thermal state and its relationship to regional tectonics in the region. The new heat flow data are collected and combined with previously published data to obtain the new heat flow map of western Anatolia. Analysis of data sets after appropriate corrections yields a better picture of the regional distribution of heat flow within the region. Generally, high values are observed around the grabens of Menderes Massif due to the intense tectonic activity. We also present the 2D steady-state thermal model of Gediz. The modeled temperatures are validated by temperature measurements from two deep wells. Numerical simulation results show that the dominant heat transfer mechanism in Gediz graben can be explained by conduction. Temperature distribution in the deep subsurface of the graben is controlled by both thickness distribution and thermal properties of the different stratigraphic sections. Thermal conductivity contrast between different stratigraphic sections causes anomalously elevated heat flow values at the edges of the graben. The comprehensive results of this study will bring a new perspective to geothermal studies in particular Enhanced Geothermal Systems (EGS) resource estimations in Gediz graben.
Keywords: Heat flow; geothermal gradient; thermal model; western Anatolia; Gediz graben; geothermal energy; CURIE-POINT DEPTH; WESTERN ANATOLIA; MENDERES MASSIF; CONDUCTIVITY; EVOLUTION; REGIONS